Magnetic molecularly imprinted polymer combined with high performance liquid chromatography for selective extraction and determination of the metabolic content of quercetin in rat plasma. Issue 1 (2nd January 2020) - Xie, Zenghui; Chen, Yanli; Zhang, Lanyun; Hu, Xujia
Abstract: In this study, a novel magnetic solid phase extraction adsorbent was prepared, namely Fe3 O4 @SiO2 as the carrier, quercetin as the template molecule, acrylamide (AM) as the functional monomer, ethylene glycol dimethacrylamide (EGDMA) as the crosslinker, 2, 2′-azo bis isobutyronitrile (AIBN) as the initiator to prepare magnetic molecularly imprinted polymer (MMIPs) with specific adsorption of quercetin by surface molecular imprinting technique. MMIPs were characterized by Fourier transform infrared spectrometer (FT-IR), X-ray diffraction (XRD) and transmission electron microscope (TEM). The binding properties of MMIPs were evaluated by isothermal adsorption, kinetic adsorption and selective adsorption experiments. The results showed that the saturated adsorption capacity and adsorption time were 17.9 μmol/g and 20 min, respectively, and showed high selectivity for quercetin. Under optimized conditions, the limit of detection (LOD) and limit of quantitation (LOQ) were 55.327 ng/mL and 184.413 ng/mL, respectively. The recovery and RSD were 85.34–95.67% and 3.36–6.59, respectively. We successfully combined magnetic solid phase extraction with high performance liquid chromatography (MSPE-HPLC-UV) for the enrichment, separation and detection of quercetin in rat plasma. The results showed that the peak and half-life of quercetin in plasma were 1.5 h (32.310 μg/mL) and 3 h, respectively. The method was simple, rapid and efficient, and could be applied to the separation and detection of quercetin in complex matrices, and also provides a basis for the separation and identification of other natural chemical components.